Thiamine-Mediated Microbial Interaction between Auxotrophic Rhodococcus ruber ZM07 and Prototrophic Cooperators in the Tetrahydrofuran-Degrading Microbial Community H-1 - Hui Huang; Hao Wu; Minbo Qi; Haixia Wang; Zhenmei Lu (Microbiology Spectrum, 2023)
ABSTRACT As a crucial growth factor, thiamine can regulate functional microbial communities; however, our current understanding of its effect on bioremediation is lacking. Using metatranscriptome and 16S rRNA gene sequencing, we explored the mechanism of response of an efficient tetrahydrofuran (THF)-degrading microbial culture, designated H-1, to exogenous thiamine. Rhodococcus ruber ZM07, a strain performing the THF degradation function in H-1, is a thiamine-auxotrophic bacterium. Furthermore, thiamine affected the microbial community structure of H-1 by altering resource and niche distributions. A microbial co-occurrence network was constructed to help us identify and isolate the cooperators of strain ZM07 in the microbial community. Based on the prediction of the network, two non-THF-degrading bacteria, Hydrogenophaga intermedia ZM11 and Pigmentiphaga daeguensis ZM12, were isolated. Our results suggest that strain ZM11 is a good cooperator of ZM07, and it might be more competitive than other cooperators (e.g., ZM12) in cocultured systems. Additionally, two dominant strains in our microbial culture displayed a “seesaw” pattern, and they showed completely different responses to exogenous thiamine. The growth of the THF degrader ZM07 was spurred by additional thiamine (with an increased relative abundance and significant upregulation of most metabolic pathways), while the growth of the cooperator ZM11 was obviously suppressed under the same circumstances. This relationship was the opposite without thiamine addition. Our study reveals that exogenous thiamine can affect the interaction patterns between THF- and non-THF-degrading microorganisms and provides new insight into the effects of micronutrients on the environmental microbial community. IMPORTANCE Auxotrophic microorganisms play important roles in the biodegradation of pollutants in nature. Exploring the interspecies relationship between auxotrophic THF-degrading bacteria and other microbes is helpful for the efficient utilization of auxotrophic functional microorganisms. Herein, the thiamine-auxotrophic THF-degrading bacterium ZM07 was isolated from the microbial culture H-1, and the effect of thiamine on the structure of H-1 during THF bioremediation was studied. Thiamine may help ZM07 occupy more niches and utilize more resources, thus improving THF degradation efficiency. This research provides a new strategy to improve the THF or other xenobiotic compound biodegradation performance of auxotrophic functional microorganisms/microbial communities by artificially adding special micronutrients. Additionally, the “seesaw” relationship between the thiamine-auxotrophic strain ZM07 and its prototrophic cooperator ZM11 during THF bioremediation could be changed by exogenous thiamine. This study reveals the effect of micronutrients on microbial interactions and provides an effective way to regulate the pollutant biodegradation efficiency of microbial communities.